2015
DOI: 10.1155/2015/542013
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume and Platelet Distribution Width as Markers in the Diagnosis of Acute Gangrenous Appendicitis

Abstract: Introduction. Acute gangrenous appendicitis (AGA) is a common medical condition; however, the grade of appendicitis usually cannot be established preoperatively. We have attempted to identify some indicators, such as the mean platelet volume (MPV) and the platelet distribution width (PDW), to diagnose AGA. Aims. To evaluate whether or not the MPV and PDW are suitable markers to diagnose AGA. Methods. A retrospective study of 160 patients with AGA and 160 healthy patients was undertaken. Disease diagnosis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
3
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 16 publications
4
31
3
8
Order By: Relevance
“…[7] However, diagnosis of appendicitis usually cannot be evaluated only based on these examinations. [8] Multiple scoring systems, such as the Alvarado and modified Alvarado scoring systems, have been used to improve the accuracy of diagnosis of acute appendicitis. [9][10][11] These scoring systems have proven successful in Western countries; however, when applied in different environments, such as the Middle East and Asia, sensitivity and specificity levels achieved have been very low.…”
Section: Discussionmentioning
confidence: 99%
“…[7] However, diagnosis of appendicitis usually cannot be evaluated only based on these examinations. [8] Multiple scoring systems, such as the Alvarado and modified Alvarado scoring systems, have been used to improve the accuracy of diagnosis of acute appendicitis. [9][10][11] These scoring systems have proven successful in Western countries; however, when applied in different environments, such as the Middle East and Asia, sensitivity and specificity levels achieved have been very low.…”
Section: Discussionmentioning
confidence: 99%
“…Complete blood count (CBC) is in the first line of laboratory evaluation to diagnose appendicitis (6,7). White blood cell count (WBC) is studied well in the literature, but recently, there are several CBC parameters such as red blood cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW) associated with the diagnosis of appendicitis (8)(9)(10)(11). In recent studies, neutrophil-to-lymphocyte ratio (NLR) is reported associated with several surgical clinical conditions as appendicitis, acute mesenteric ischemia, and strangulated inguinal hernia (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…There are other studies supporting this conclusion (11,16,17). In contrast to both studies, other studies with larger patient groups reported no changes in MPV values (13,18,19).…”
Section: Discussionmentioning
confidence: 66%
“…In a study of 295 patients in 2015, Uyanik et al (20) reported a statistically significant decrease in MPV values together with a decrease in PDW. In contrast, Fan et al (17) reported a statistically significant increase in PDW values and a statistically significant increase in MPV values in AA patients. In contrast to several previous studies, our findings indicate that platelet markers such as PDW, PCT and MPV are not useful in the diagnosis of AA and in predicting its severity, since they exhibit a hemodilutional decrease related to hydration therapy.…”
Section: Discussionmentioning
confidence: 82%